Evaluation of Early Screening for Mental Emotional Problems after the Covid-19 Pandemic in Preschool Children - Esme Anggeriyane (P3M Universitas 'Aisyiyah Surakarta, 2023)
Mental and emotional problems at every age level are increasing and exacerbated by the Covid-19 pandemic. The Covid-19 pandemic from 2019 to 2022 affects the growth and development of preschool children. Growth and development are influenced by mental and emotional problems of children so the importance of early screening to detect in children aged 36-72 months. This study aimed to determine the description of early screening for mental-emotional problems in preschool children at Margo Utomo Kindergarten, Puntik Dalam Village due to the Covid-19 pandemic. The design of this research was descriptive-quantitative. The screening was carried out on 40 children by interviewing with parents based on guidelines of the Ministry of Health of the Republic of Indonesia in 2016 regarding the Mental Emotional Problem Questionnaire with totaling 14 questions, answer choices